Argentinean National Plant Protection Network Website - Gasoni, Amelia Laura (2017)
The Argentinean National Plant Protection Network (RedNPV) was created in 2006 as a proposal of the National Plant Protection Program (PNPV), National Institute of Agricultural Technology (INTA). The National Plant Protection Network (RedNPV) main objective is to articulate national scientific-technological capabilities in Plant Protection. Although it was created by INTA, this network attempts to integrate plant pathology working groups from different scientific-technological institutions as universities and public and private research institutes related to Plant Protection. The RedNPV also promotes the articulation of different research institutions to proactively address plant protection problems and management of organisms that are harmful to agriculture through strategies economically and environmentally sustainable. As a harmful organisms we include weeds, pests and plant pathogens already established, those of quarantine importance and also the emerging ones, Crop pests (arthropods, nematodes, fungi, viruses, phytoplasms, weeds) are responsible for significant losses in crop production and affect both domestic and export crops. The RedNPV facilitates access to knowledge about new pests and research activities in the National Plant Protection Program Projects. Another remaining aspect of the Network is the publication of protocols obtained in the Specific Projects; and updating the database, laboratories, and publications .